Synthesis and Spectral Analysis of Mn (II), Cu (II) ,Ni (II) and Cd (II) Complexes with Mixed Ligands containing 1,10-phenanthroline and Schiff base derived of 4-aminoantipyrine - Baghdad Science Journal (مجلة بغداد للعلوم)
The complexes of Schiff base of 4-aminoantipyrine and 1,10-phenanthroline with metal ions Mn (II), Cu (II), Ni (II) and Cd (II) were prepared in ethanolic solution, these complexes were characterized by Infrared , electronic spectra, molar conductance, Atomic Absorption ,microanalysis elemental and magnetic moment measurements. From these studies the tetrahedral geometry structure for the prepared complexes were suggested.The prepared ligand of 4-aminoantipyrine was characterized by using Gc-mass spectrometer .